PENGEMBANGAN MODEL STRATEGI PEMASARAN DIGITAL YANG EFEKTIF PADA PERBANKAN SYARIAH DI INDONESIA DI ERA DIGITAL - Rafli Faisal Firdaus; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
Global economic developments have had a significant impact, especially in the field of digital transformation in various fields, including the banking sector. In the digital era, especially in Islamic banking, they are able to adapt and improve their marketing strategies. Digital marketing strategies are the main factor in achieving success in today's digital era. This abstract discusses digital marketing strategies that can be applied by Islamic banks in facing fierce competition in this digital era. This study analyzes several effective digital marketing strategies such as website marketing, use on social media (Instagram, Facebook, Twitter, etc.) and use on other digital platforms. In addition, this study will also examine what are the challenges and opportunities for Islamic banks when implementing this digital marketing strategy. The results of this study are expected to provide several recommendations for implementing effective digital marketing strategies in Islamic banks.